Effect of Juglans regia L. Ridge on Blood Lipids in Type 2 Diabetic Patients with Dyslipidemia: A Double-blind Placebo-Controlled Randomized Clinical Trial - Mehrzad Mirshekari; Arman Zargaran; Nooshin Shirzad; Mahboobeh Hemmatabadi; Mahnaz Khanavi; Mahbube Ebrahimpur; Fatemeh Afra; Soha Namazi (Tabriz University of Medical Sciences, 2023)
Background: Dyslipidemia and diabetes mellitus are two important risk factors for coronary artery disease and stroke. Traditionally, herbal remedies like walnut were used to treat dyslipidemia. The study aimed to evaluate the effect of Juglans regia L. (J. regia L.) internal septum extract (ISE) on lipid profile of patients with type 2 diabetes. Methods: After preparing hydroalcoholic ISE, Folin-Ciocalteau (FC) and AlCl3 colorimetric methods were used to determine total phenolic content (TPC) and total flavonoid content (TFC), respectively. In a randomized, double-blind placebo-controlled trial, 86 diabetic patients with dyslipidemia were randomly divided into equal groups and received ISE or placebo capsules 1500 mg/day for 12 weeks. Lipid profile, LFT, SCr, urea, hemoglobin A1c (HbA1c), blood pressure (BP), weight, waist and waist to hip ratio (WHR) were determined at baseline and after 12 weeks. The paired sample t-test and independent sample t-test were performed to compare the differences within and among the groups, respectively. This study was registered in the Iranian registry of clinical trials (IRCT ID: IRCT20201227049850N1). Results: The mean (SD) of TPC and TFC were measured based on 74.57 (5.20) milligram gallic acid equivalent/gram of dry extract (mg GAE/g DE) and 14.11 (2.73) mg quercetin equivalent/g of DE (mg QE/g DE), respectively. During the trial, 26 patients lost follow-up, and the study continued with remaining 60 patients. After intervention, there were no significant differences in LDL-C (p=0.44), total cholesterol (TC) (p=0.42), high-density lipoprotein cholesterol (HDL-C) (p=0.99), triglyceride (TG) (p =0.32) and Lp(a) (p=0.55) between two groups. Moreover, no significant (p>0.05) changes were observed in HbA1c, LFT, SCr, urea, BP, weight, waist, and WHR among the groups after 12 weeks. Conclusion: Our findings showed J.regia L. ISE had no significant effect on lipid profile compared to placebo. Moreover, no adverse effect was observed on liver and kidney function tests.